Membangun Kepercayaan Diri dan Kemampuan Berbahasa Inggris Melalui Program Role Play dalam English Talent Show di SMPN 4 Kuningan - Afla, Nurul; Anggy MZ, Liza; Salihah, Mita; Husein , Muhammad; Nugroho, Muhammad Aprianto Budie (Jurnal Pengabdian kepada Masyarakat Radisi, 2025)
This community service activity aims to improve students' self-confidence and English language skills through the Role Play program in the English Talent Show at SMPN 4 Kuningan. This experience-based program encourages students to use English in a dramatic and collaborative context. The stages of the activity include story selection, role assignment, scenario preparation, training, staging, and reflective discussion, with guidance from PPG Pre-Service students and supervising teachers. Data were collected through observation, interviews with teachers and school management, and visual documentation. The results showed an increase in speaking fluency, understanding of dialogue structures, and emotional expression in English. Students also developed in social aspects such as collaboration and leadership. Based on the analysis of Vygotsky, Kolb, Krashen, and Maley & Duff theories, this program proves the effectiveness of drama as an integrative learning strategy that combines linguistic, affective, and social aspects, and is recommended for application in language learning in secondary education.